Politolana sanchezi sp. nov. (Crustacea: Isopoda: Cirolanidae), a new benthic bioturbating scavenger from bathyal soft-bottoms of the southern Bay of Biscay (northeastern Atlantic Ocean) - Frutos, Inmaculada; Sorbe, Jean Claude (Zootaxa, 2010)
A new species of the genus Politolana (Crustacea, Isopoda, Cirolanidae) is described, based on specimens collected from the Le Danois Bank (‘El Cachucho’ fishing ground), southern Bay of Biscay, northeastern Atlantic Ocean. Politolana sanchezi sp. nov. can be distinguished from P. microphthalma (the only Politolana species recorded in boreal European waters) by larger eyes, presence of chromatophores on pereon and pleon, antennae reaching to the middle of the second pereonite, lateral margin of the frontal ridge dividing eyes, superior meral lobe of pereopod 1 reaching midpoint of the propodus, distal end of uropodal endopod subacute and pleotelson apex broadly convex with small medial point. An identification key to the world species of Politolana is presented. The new species has been found living on muddy-fine sandy bottoms of the southern Bay of Biscay and western Galicia, between 480 and 791 m depth. According to the present findings, it belongs to the benthic scavenger guild recognized on continental slopes. Its scavenging and bioturbating behaviour at the sediment-water interface are described from in situ trophic experiments with a fish-baited trap combined with a time-lapse recording camera.